The Serbian Orthodox Church and policy of the Serbian authorities after 2000 - Korzeniewska-Wiszniewska, Mirella (Balcanica Posnaniensia. Acta et studia, 2010)
The article analyzes the position of the Serbian Orthodox Church (SOC) in relation to the political transformations in the Republic of Serbia after 2000, that is, after the fall of Slobodan Milošević’s regime and the rise of the democratic opposition. The author places the issue in a broader historical context, emphasizing that the contemporary relations between the Church and the state stem from the experiences of the 1990s, when the SOC, identifying itself with the national idea, played a significant role in the armed conflicts accompanying the disintegration of Yugoslavia. The study aims to show to what extent the Serbian Church adapted to the new political realities, marked by democratization and European integration, and which areas remained sources of tension between the secular and clerical spheres. The research is based on the analysis of official SOC publications, including statements and materials posted on its website, as well as scholarly works concerning church–state relations in Serbia and the Balkans. The findings indicate that, despite formally supporting the post-2000 authorities, the SOC retained an ambivalent stance toward Western-oriented reforms and the idea of Europeanization. The Church continued to focus on national issues, particularly the question of Kosovo, the defense of Serbian religious identity, and maintaining close ties with Russia. At the same time, radical and anti-Western tendencies persisted within its ranks. The author concludes that the SOC remains a significant actor in Serbia’s political life-a guardian of tradition and national identity-yet its vision of statehood and society often conflicts with the liberal-democratic trajectory pursued by Serbian authorities after 2000.